Civil construction waste in the municipality of Tucuruí-PA: analysis and contributions for a generic proposal for a management plan - Siqueira, Rafaela Ribeiro; Macedo, Alcebíades Negrão (Brazilian Journal of Production Engineering, 2023)
The reality of many Brazilian municipalities, including Tucuruí in the State of Pará, Brazil, does not present a CCR management adequate to its situation. Even if it is necessary to comply with the legal requirements that punctuate the management of RCC, such as the elaboration of a management plan for civil construction waste that is accessible and applicable to the real needs of each municipality. As a way of understanding the situation, the research in question was proposed, with the main objective of subsidizing the creation of a generic RCC management plan. For the realization of the work, the methodology used in terms of the type of approach is qualitative and quantitative, in terms of its nature, it is considered applied and in terms of technical procedures, it is characterized as a case study. Within this line of reasoning, with a view to identifying the impacts caused, indirect interviews were carried out with managers of public and private bodies, as well as on-site analysis. Therefore, the work through the analysis of the scenario found reaffirms the need for reduction, reuse, recycling, reuse and the environmentally correct destination of RCC, in this way, the strategies proposed in the plan will be able to assist in the physical, political, socio-environmental and economic aspects of Tucuruí-PA.
Keywords: Construction waste; Waste Management; Tucuruí-PA